The structure / anti-structure of October Revolution celebration on late Soviet periodical press (on materials from Tomsk) - A. D. Moiseenko (Омский научный вестник: Серия "Общество. История. Современность")
The celebration of the October Revolution in the late Soviet period (1968–1984) is explored in this article. The empirical ground of the research is based on materials from the Tomsk periodical press. The theoretical foundations fit into the framework of the historiographic discussion between Aleksey Yurchak (the concept of the perfomative shift of ideological discourse) and Caroline Humphrey (the idea of a «creative» initiative based on the mimesis strategy). The holiday context is studied through the triad «structure–hyperstructure–anti-structure», which explains the stages of the celebration that existed during the researching period. The author poses the problem of the logic of constructing and reproducing the basic mechanisms of celebratory action on local material. Actualization of the research is considered through the situation of the modern status of commemorative spaces of «trauma» and «nostalgia» regarding the events of the October Revolution. The main research conclusions are related to determining the boundaries of the triad of celebratory actions and utterances under consideration. According to the source material, the combination of mechanisms for the implementation of hyperstructure and anti-structure of the celebration of the October Revolution Day reproduced the basis of the celebration — «structure» (which, by definition, should be a reflection of Soviet reality itself). So, the late Soviet celebration of the October Revolution did not reflect the principles of the classical «ritual process» (according to V. Turner)